2018
DOI: 10.1038/s41598-018-25760-7
|View full text |Cite
|
Sign up to set email alerts
|

Different rearing conditions alter gut microbiota composition and host physiology in Shaoxing ducks

Abstract: Emerging evidences have linked the gut microbiota to poultry physiology. Gut microbiota composition in Shaoxing ducks were profiled under different rearing conditions: raised on the litter floor and the plastic mesh floor. A total of 46 and 39 luminal content samples from the duodenum, ileum, and cecum of the ducks reared under the two conditions were analyzed by 16S rRNA gene amplicon sequencing analysis. Proteobacteria (48.66%), Proteobacteria (33.38%), and Bacteroidetes (55.35%) were the dominant phyla in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 47 publications
7
36
1
1
Order By: Relevance
“…In the present study, Firmicutes, Proteobacteria, Bacteroidetes, Cyanobacteria, and Actinobacteria were the major phyla in the GIT of duck, which suggested that the dominant phyla in the duck GIT are similar to those in other poultry, including turkeys, geese, and chickens ( Qu et al., 2008 , Scupham et al., 2008 , Waite and Taylor, 2015 , Xiao et al., 2017 , Yang et al., 2018a ). Bacteroidetes in the cecum of duck was considerably more abundant than that in other sections, which is similar to the findings of several previous studies ( Vasaï et al., 2014a , Vasaï et al., 2014b , Wang et al., 2018 ). However, Best et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, Firmicutes, Proteobacteria, Bacteroidetes, Cyanobacteria, and Actinobacteria were the major phyla in the GIT of duck, which suggested that the dominant phyla in the duck GIT are similar to those in other poultry, including turkeys, geese, and chickens ( Qu et al., 2008 , Scupham et al., 2008 , Waite and Taylor, 2015 , Xiao et al., 2017 , Yang et al., 2018a ). Bacteroidetes in the cecum of duck was considerably more abundant than that in other sections, which is similar to the findings of several previous studies ( Vasaï et al., 2014a , Vasaï et al., 2014b , Wang et al., 2018 ). However, Best et al.…”
Section: Discussionsupporting
confidence: 91%
“…Different gastrointestinal sections have different microbial community structures and play different roles in the health and growth of poultry ( Lee and Pang, 1992 , Pan and Yu, 2014 ). Although the microbial community of the duck GIT has already been reported, previous studies have mainly focused on the part of intestinal sections and feces ( Sun et al., 2016 , Best et al., 2017 , Dai et al., 2018 , Wang et al., 2018 ). In the present study, we have investigated the microbial composition in the GIT of duck, including the proventriculus, gizzard, duodenum, jejunum, ileum, cecum, and rectum through 16S rRNA gene sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…We found that more than 20 kinds of known phylum and more than 1300 kinds of known genus could be carried in migratory birds by 16S rDNA analysis of migratory birds epidemic material and stool ( Supplement Table S3 ). Our results were consistent with studies on the intestinal bacteria of swan and mallard, the dominant phylum of them were Proteobacteia, followed by Bacteroidetes and Firmicutes [13,14]. At the same time, the water environment as the main source of migratory bird diet, it played an important role in the composition of migratory bird gut microbiota [15].…”
Section: Discussionsupporting
confidence: 91%
“…However, information on the effects of feeding patterns on the intestinal environment and the composition of the intestinal microbiota is still lacking. To the best of our knowledge, only some studies have examined the effect of rearing conditions on the intestinal microbiota in chickens or ducks ( Xu et al, 2016 ; Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%